Profil Endapan Nikel Laterit di Kecamatan Tinanggea, Kabupaten Konawe Selatan, Provinsi Sulawesi Tenggara - Hasria Hasria; Suryawan Asfar; Ervan Rizqullah Tawakkal (PROMINE, 2021)
The research area is located in Tinanggea District, South Konawe Regency, Southeast Sulawesi Province. This study aims to determine the profile of laterite nickel deposits in the study area. The research method used consists of literature study, field sampling and laboratory analysis and data interpretation. The results showed that the profiles of laterite nickel deposits in the study area consisted of top soil, limonite zone, saprolite zone and bedrock with different thicknesses. Top soil at Station 1 is very thin in the form of clay and plant remains, while at Station 2 it is a layer of sediment (limestone) with a thickness of 0-5 meters. Based on geochemical data, it shows that Ni, SiO and MgO elements /oxides show enrichment in the saprolite zone because have mobile so its dissolve easily during the laterization process and are transported the subsurface and experience leaching so that its are concentrated in the saprolite zone. The Fe element shows enrichment in the limonite zone because the Fe element has immobile so that it is not easily transported downward and is concentrated in the upper zone, namely the limonite zone.